Ecotourism between theory and practice: empirical analysis of the tourism industry of whale watching in Húsavík (Iceland) - NICOSIA, ENRICO DOMENICO GIOVANNI; Perini, Francesco (2016)
Whale watching is a dynamic industry and, in particular in a country like Iceland, where tourism is currently playing a leading role in the national economy and where nature – understood in a broad sense – represents the main attraction for visitors, whale watching, rapidly grown during the last years, shows an evident potential under an ecotouristic point of view. In recent times, an increasing need for the understanding of interactions between humans (tourists) and wildlife (whales) emerged, highlighting the interest towards environmental conservation, protection and preservation matters and towards the search for activities, and modalities, that could essentially contribute to the sustainability of tourism experiences, such as wildlife tourism ones. It is difficult to argue with the fact that whale watching uses the whale “asset” in a non-destructive way, unlike whaling, activity still commercially conducted in Iceland, but at the same time it can’t be considered ecotouristic and sustainable a priori. In fact, several studies point out how tourism has a disturbing effect on wildlife and negatively affects their ecology and short- to long-term behaviours. This article, after a general introduction on the main ecotourism principles, examines the whale watching industry of the “Whale Capital of Iceland”, Húsavík, and it mainly focuses on the results and data of two researches conducted in the field – respectively among whale watchers and among the local whale watching companies. The purpose of this work is to investigate if and how Húsavík whale watching is following an environmentally sustainable and ecotouristic path, and to bring into light its strengths and weaknesses as a whale watching destination.